Evaluation of a Novel Cone Beam Computed Tomography Scanner for Bone Density Examinations in Preoperative 3D Reconstructions and Correlation with Primary Implant Stability. (27th December 2013) - Sennerby, Lars; Andersson, Peter; Pagliani, Luca; Giani, Claudio; Moretti, Giacomo; Molinari, Massimo; Motroni, Alessandro
Abstract: Background: Bone density examination (BDE) using preoperative cone beam computed tomography (CBCT) might be used to predict primary implant stability in implant patients. Purpose: The aim of the study was to validate a novel CBCT scanner in vitro with regard to BDE in preoperative scans and to analyze the in vivo correlation of CBCT scan results with primary implant stability measurements. Materials and Methods: A CBCT scanner was validated in vitro with regard to spatial uniformity and linearity of CT numbers (Hounsfield units, HU) by using a series of phantoms and plastic and hydroxyapatite specimens of various densities. Forty‐nine patients (27 female and 22 male, mean age 55.6 ± 9.8) were scanned prior to and 1 to 6 months after the placement of 155 dental implants of different lengths and diameters. Mean and peak insertion torque (IT) in Ncm were registered during implant placement. Resonance frequency analysis (RFA) measurements in ISQ units were performed after placement. The second scan was used to export and superimpose the exact positions of bone and implants into the first scan. Virtual probes with the same length as the actual implant were automatically placed at the implant sites, and mean HU values were measured in a 1 mm–wide circular corridor from the tip of the threads and out. Results: The in vitro validation showed high uniformity and linearity of CT numbers (HU). The clinical study showed significant correlations between bone density and ISQ, mean IT, and peak IT, respectively. Conclusions: The WhiteFox CBCT scanner measures bone density with high accuracy. There is a correlation between bone density and primary implant stability as assessed with IT and RFA measurements. The findings suggest that BDE may be used as an additional feature in treatment‐planning software to estimate primary stability at predetermined implant sites.